The Legacy of Sukarno’s Support for Palestine: How Indonesia's First President Shaped Contemporary Solidarity (Palestine Issues on Indonesian Society, 2024)
This paper offers a historical analysis of President Sukarno’s unwavering support for Palestine and examines how his legacy continues to shape Indonesia’s contemporary stance on Palestinian issues. Sukarno’s foreign policy, grounded in anti-colonialism and solidarity with oppressed nations, provided a foundational framework for Indonesia’s pro-Palestinian stance. The paper traces the evolution of this policy from Sukarno’s era to the present, focusing on key moments in Indonesia’s diplomatic engagement with Palestine and its representation in public discourse. Through archival research and a review of speeches, diplomatic correspondence, and media portrayals, the study highlights how Sukarno’s rhetoric—particularly his framing of Palestine as a symbol of global resistance against imperialism—resonates with current Indonesian foreign policy. The paper also examines how Sukarno’s legacy is invoked in contemporary political debates, particularly within nationalist and Islamic movements in Indonesia. The research reveals how Sukarno’s advocacy for Palestinian statehood has been institutionalized in Indonesia's diplomatic narrative and remains a central component of Indonesia’s identity as a leader of the Global South.